2017
DOI: 10.1093/jnci/djx005
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Human Papillomavirus Type 16 E6 Antibody Response Prior to Oropharyngeal Cancer

Abstract: Forty-two percent of subjects diagnosed with OPC between 1994 and 2009 in a US cohort were HPV16-E6 seropositive, with stable antibody levels during annual follow-up for up to 13 years prior to diagnosis. Tumor analysis indicated that the sensitivity and specificity of HPV16-E6 antibodies were exceptionally high in predicting HPV-driven OPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
124
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(134 citation statements)
references
References 29 publications
6
124
0
4
Order By: Relevance
“…8 Using the same multiplex assay, these results were validated in Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) where antibody levels were found to remain elevated and stable for up to 13 years prior to diagnosis. 12 Moreover, the 10-year cumulative incidence of OPC among seropositive individuals 6.2% among men and 1.3% among women. 12 In a previous study of 256 OPC cases and 250 controls, we found that seropositivity for E2, E6, and/or E7 was associated with OPC risk (OR, 249.1; 95% CI, 99.3-624.9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Using the same multiplex assay, these results were validated in Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial (PLCO) where antibody levels were found to remain elevated and stable for up to 13 years prior to diagnosis. 12 Moreover, the 10-year cumulative incidence of OPC among seropositive individuals 6.2% among men and 1.3% among women. 12 In a previous study of 256 OPC cases and 250 controls, we found that seropositivity for E2, E6, and/or E7 was associated with OPC risk (OR, 249.1; 95% CI, 99.3-624.9).…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, the 10-year cumulative incidence of OPC among seropositive individuals 6.2% among men and 1.3% among women. 12 In a previous study of 256 OPC cases and 250 controls, we found that seropositivity for E2, E6, and/or E7 was associated with OPC risk (OR, 249.1; 95% CI, 99.3-624.9). 9 Our current results are consistent with these previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis projects noteworthy incidence rates of OPC in HPVunvaccinated US white men over the coming decades ( Fig. 17,18 The detection of HPV in oral samples may be attractive as a research tool because noninvasive mouthwash and gargle specimens are simple to obtain. 1).…”
Section: Incidence and Survival Rates For Opcmentioning
confidence: 97%
“…Viral integration in the host cells and additional risk factors including a twisted T-cell homeostasis might support HPV persistence in the tonsils which over time eventually leads to HPV-associated OPSCC. This could also neatly explain why high titers of HPV16 E6 antibodies have been shown to predict the development of incident HPV-driven OPSCC even 10–15 years in advance [79, 104]. …”
Section: The New Hypothesismentioning
confidence: 99%